Biochemistry and molecular biology of fishes (Elsevier, 1994)
This third volume in the series covers such topics as anaesthetics, cannulation and injection techniques, and surgery. The book will be invaluable to fisheries scientists, aquaculturists, and animal biochemists, physiologists and endocrinologists; it will provide researchers and students with a pertinent information source from theoretical and experimental angles.,This third volume in the series covers such topics as anaesthetics, cannulation and injection techniques, and surgery. The book will be invaluable to fisheries scientists, aquaculturists, and animal biochemists, physiologists and endocrinologists; it will provide researchers and students with a pertinent information source from theoretical and experimental angles.